Síntese de derivados pirazolidínicos e avaliação da atividade antibacteriana - (:unkn) unknown (Universidade Estadual de Goiás, 2012)
Pyrazolines compounds are a class of molecules that has been the subject of research in search of new compounds prototypes with biological activity. This paper reports studies of the synthesis, structural characterization and evaluation of the antibacterial activity of acetylated and non-acetylated pyrazoles obtained of chalcones. In the first step were synthesized from chalcones the general reaction of aldol condensation via the Claisen-Schmidt acid and base catalysis using nitroacetophenones, aminoacetophenone, methoxyacetophenones, methylacetophenones, fluoroacetophenones and acetophenones by varying the substituted benzaldehydes. A second step acetylated pyrazoles were obtained from the reaction of substituted chalcones with hydrazine in acetic acid in refluxing. Later, another procedure was performed to obtain pyrazoles without the acetyl grouping from the reaction of chalcones with hydrazine in ethanol medium on reflux. The results of 1H NMR, 13C NMR, IV and CG confirm the formation of products with high purity. From these results it was concluded that the methodology produces good results to obtain the pyrazoles. The biological tests will be conducted from the microplate-based spectrophotometric method for evaluation of the antibacterial activity of the molecules obtained. The results show that the activity of the prototypes is related to the type of substituent group present on the ring. Some prototypes demonstrated antibacterial activity with CMI ranging from 62.5 to 250 ug / mL, and thus a significant result to demonstrate the ability of antibacterial molecules tested.
Keywords: Pirazóis; Chalconas; Atividade Biológica; Antibacteriana; Pyrazoles; Chalcones; Biological Activity; Antibacterial; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA